OPTIMALISASI PENGGUNAAN MEDSOS BRANDING PRODUK UMKM DI DI DESA KALANGANYA KECAMATAN SEDATI SIDOARJO - Enny Istanti; Agus Mahmdi (Universitas 45 Surabaya, 2022)
Social media is a media that is born and will continue to develop over time as one of the most popular alternatives for means of communication, interacting, sharing, participating, creating something new that is more impressive and also a means of working without being limited by space and time. . MSMEs are small business activities that can provide great benefits from the economic side. Social media is used by MSME actors to be bolder in promoting their products as a fast, effective and efficient marketing tool. With the existence of MSMEs, it is expected to be able to create jobs, increase income and encourage the realization of national stability. This community service activity is in the form of socialization and training on the development of MSME marketing in Kalanganyar Village through social media